Idiopathic Ventricular Arrhythmias Ablated in Different Subregions of the Aortic Sinuses of Valsalva: Anatomical Distribution, Precordial Electrocardiographic Notch Patterns, and Bipolar Electrographic Characteristics - Weng, Sixian; Zhai, Zhengqin; Tang, Min; Zhou, Bin; Ding, Lei; Yu, Fengyuan; Qi, Yingjie; Zhang, Hongda; Feng, Tianjie; Zhang, Shu (Frontiers in Cardiovascular Medicine, 2021)
Background: Little is known about the differences among ventricular arrhythmias (VAs) ablated in different subregions of the aortic sinuses of Valsalva (ASVs). We aim to investigate the distribution, precordial electrocardiographic patterns, and bipolar electrogram characteristics of VAs ablated in different subregions of the ASVs. Methods: We divided the right ASV and the left ASV into a total of 6 subregions and studied 51 idiopathic VAs ablated first time successfully in the ASVs. Results: These 51 VAs were inhomogeneously distributed among the 6 subregions, which comprised the right-lateral ASV (1/51), the right-anterior ASV (11/51), the regions along the right (13/51) and left (9/51) sides of the ASV junction, the left-anterior ASV (5/51), and the left-lateral ASV (12/51). Fractionated potentials were dominant (39/51, 76%) among the 3 types of target electrograms. From the right-lateral ASV to the left-lateral ASV, the percentage of fractionated potentials gradually decreased from 100 to 59%. A precordial rebound notch in V3-V4 or V4-V5 had sensitivity of 90.9%, specificity of 85.0%, and negative predictive value (NPV) of 97.1% to predict VAs ablated in the right-anterior ASV. A precordial rebound notch in V2-V3 had sensitivity of 50.0%, specificity of 94.9%, and NPV of 86.0% to predict VAs ablated in the left-lateral ASV. Conclusion: VA targets were mainly distributed in the anterior and the left-lateral ASVs. Fractionated potentials were common among target electrograms, especially in theright-anterolateral ASV. Precordial electrocardiographic rebound notch has high predictive accuracy in identifying different subregions of the ASVs as target ablation sites.